Combined effects of oat bran supplementation and jogging exercise on body composition, blood lipid profiles and cardiorespiratory endurance in female university students - Hamzah, Muhammad Alif Ridzuan (Pusat Pengajian Kesihatan, 2015)
It is known that beta-glucan in oat bran could reduce level of total cholesterol (TC), triglycerides (TG) and low density lipoprotein cholesterol (LDL-C) and increase high density lipoprotein (HDL-C). Meanwhile, aerobic exercise is known to be beneficial to improve body composition and increase maximum oxygen uptake (VO2max). However, the additional combined effect of oat bran supplementation and aerobic exercise is still lacking. To investigate the effectiveness of combined oat bran supplementation and jogging exercise compared to oat bran supplementation alone or jogging exercise alone on body composition, lipid profiles and cardiorespiratory endurance in female university students. 48 female university students were randomly assigned to 4 groups: control (C), oat bran supplementation alone (Ob), Exercise alone (Ex) and combined oat bran and exercise (ObEx) groups. Pre- and post tests were carried out to measure participants’ body anthropometry, body composition, blood lipid profiles and predicted VO2max. During the intervention period, participants in Ob and ObEx groups consumed oat bran daily for 6 weeks. Participants in ObEx consumed oat bran 1 hour before jogging exercise on the exercise days. Participants in Ex and ObEx groups carried out jogging exercise 3 days per week for 6 weeks. There were no significant changes in percentage body fat and fat free mass in all groups. Statistically, significant reductions in TC (-13.57%), TG (- 20.65%), LDL-C (-10.77%) and V02max (5.9%) were observed in ObEx group. In Ob group, there were significant reduction in TC (-11.42%) and LDL-C (- 9.16%). Similarly, significant reductions in TC (-9.43%) and LDL-C (-8.0%) were also observed in Ex group. ObEx group showed significant increase in VOsmax and the increase in VChmax was the highest among all the groups. Combination of oat bran supplementation and jogging exercise significantly reduced level of total cholesterol, triglyceride and low density lipoprotein cholesterol, however did not affect high density lipoprotein cholesterol level. This combination also improved participant’s cardiorespiratory endurance. In general, the combination of oat bran and jogging exercise elicited more beneficial effects on blood lipid profiles and cardiorespiratory endurance compared to control, oat bran supplementation alone and exercise alone groups. Therefore, this combination can be recommended for improving lipid profiles and cardiovascular fitness in young female population.